2013
DOI: 10.1371/journal.pone.0082661
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Limitation in Three Lowland Tropical Forests in Southern China Receiving High Nitrogen Deposition: Insights from Fine Root Responses to Nutrient Additions

Abstract: Elevated nitrogen (N) deposition to tropical forests may accelerate ecosystem phosphorus (P) limitation. This study examined responses of fine root biomass, nutrient concentrations, and acid phosphatase activity (APA) of bulk soil to five years of N and P additions in one old-growth and two younger lowland tropical forests in southern China. The old-growth forest had higher N capital than the two younger forests from long-term N accumulation. From February 2007 to July 2012, four experimental treatments were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
28
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 55 publications
6
28
0
2
Order By: Relevance
“…Vitousek and Sanford (1986) found that shoot:root ratios in tropical forest decrease with decreasing soil fertility. Leuschner et al, (2007) found that the ratio of root biomass to above-ground biomass increased 10 fold with altitude in tropical forest at 1050 and 3060 m elevation, and Zhu et al (2013) found that nitrogen addition to an N-rich old growth forest decreased fine root biomass by 31%. A review of above-and below-ground production in forest ecosystems found that the highest fine root biomasses were found at locations where soils were high in Al and Fe and nutrient limited (Vogt et al, 1996).…”
Section: Insert Figure 81 Near Herementioning
confidence: 99%
“…Vitousek and Sanford (1986) found that shoot:root ratios in tropical forest decrease with decreasing soil fertility. Leuschner et al, (2007) found that the ratio of root biomass to above-ground biomass increased 10 fold with altitude in tropical forest at 1050 and 3060 m elevation, and Zhu et al (2013) found that nitrogen addition to an N-rich old growth forest decreased fine root biomass by 31%. A review of above-and below-ground production in forest ecosystems found that the highest fine root biomasses were found at locations where soils were high in Al and Fe and nutrient limited (Vogt et al, 1996).…”
Section: Insert Figure 81 Near Herementioning
confidence: 99%
“…This ecosystem, unlike ecosystems such as bogs and tropical forests that are typically P limited (i.e., high soil N:P ratio), has been found to be experiencing high P but low N in soils (Delgado-Baquerizo et al 2013). This raises the question: will N deposition be beneficial to this desert steppe, or will it lead to a similar shift from N to P limitation as has been observed in bogs and tropical forests (i. e., Phuyal et al 2008;Zhu et al 2013)?…”
Section: Introductionmentioning
confidence: 95%
“…Since N deposition affects soil N content more positively than soil C and P contents, researchers have hypothesized that excessive long term N deposition may cause an increase in the ecosystem N:P ratio, leading to N saturation and eventual P limitation (Bobbink et al 1998;van Heerwaarden et al 2003;Menge and Field 2007;Vitousek et al 2010;Li et al 2012). To date, this prediction has been tested in many ecosystem types, such as three tropical forests in southern China (Zhu et al 2013), an ombrotrophic bog in Whim Moss, Edinburgh, UK (Phuyal et al 2008), a calcareous grassland in Derbyshire Dales, UK (Phoenix et al 2004), a fire-derived and N-rich Hawaiian grassland (D'Antonio and Mack 2006), and several temperate forests (Gress et al 2007;Braun et al 2010;Naples and Fisk 2010). Despite the well-documented evidence in other ecosystems, our knowledge of the effect of N deposition remains incomplete for the desert steppe.…”
Section: Introductionmentioning
confidence: 99%
“…P addition has been suggested as an effective management practice because P addition may mitigate the negative effects caused by adding N alone, such as mitigating the decrease in litter decomposition rates [31], microbial biomass [32] and live fine root biomass [33]. According to previous studies, adding P alone seems to only affect soil phosphatase activity but not b-glucosidase activity.…”
Section: Introductionmentioning
confidence: 99%